Sand bezoar: A very rare cause of intussusception - Azhar AH,; Tarmizi MNM,; A. Rashidi,; H. Mastura,; MNG Rahman, (Department of Surgery, UKM Medical Centre, 2011)
Intussusception is the most common cause of intestinal obstruction in the first two years of life. The cause is not apparent in most of the cases. Associated conditions that can result in intussusception include polyps, Meckel’s diverticulum, Henoch-Schonlein purpura, lymphoma, lipoma, parasites, foreign bodies and viral enteritis with hypertrophy of Payer’s patches. We hereby describe a rare case of sand bezoar induced intussusception in a 9-year-old school girl with pica (geophagia). A description of her presentation and management, along with a review of literature is being presented.